IMPLEMENTASI KURIKULUM MERDEKA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI DI SMP DARUL ISHLAH TULANG BAWANG - Yulinar Mega Pratiwi; Giman Bagus Pangeran; Nur Azizeh (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Changes in the education system after the pandemic demand adjustments in the learning process, including the implementation of the Merdeka Curriculum, which emphasizes learning freedom and character strengthening. In this context, Islamic Religious Education and Character Building (PAI-BP) plays an important role in shaping students’ faith and noble character. This research is motivated by the challenges and obstacles faced in implementing the Merdeka Curriculum in educational institutions, particularly in the PAI-BP subject. The purpose of this study is to describe the implementation of the Merdeka Curriculum in PAI-BP subjects at SMP Darul Ishlah Tulang Bawang, to analyze the emerging problems, and to explain the efforts made by the school to overcome the implementation barriers. This study employed a descriptive qualitative approach with data collection techniques consisting of observation, interviews, and documentation. The data were analyzed descriptively by focusing on the implementation process and learning outcomes. The results show that the implementation of the Merdeka Curriculum at SMP Darul Ishlah Tulang Bawang has been carried out, although several obstacles remain, such as teachers’ limited understanding of the curriculum concept, insufficient facilities and infrastructure, and lack of technical training and assistance. The school’s efforts include organizing teacher workshops, enhancing creativity in developing teaching materials, and fostering collaboration among educators. This study recommends increasing training and providing better facilities to ensure that the implementation of the Merdeka Curriculum in PAI-BP can run more effectively and optimally.